2019
DOI: 10.3390/su11082254
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility (CSR) Practices of the Largest Seafood Suppliers in the Wild Capture Fisheries Sector: From Vision to Action

Abstract: Corporate social responsibility (CSR) in the seafood industry is on the rise. Because of increasing public awareness and non-governmental organization (NGO) campaigns, seafood buyers have made various commitments to improve the sustainability of their wild seafood sourcing. As part of this effort, seafood suppliers have developed their own CSR programs in order to meet buyers’ sourcing requirements. However, the CSR of these companies, many of which are mid-supply chain or vertically integrated, remain largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 80 publications
(103 reference statements)
0
19
0
1
Order By: Relevance
“…The findings of the research, although in the explorative phase, allowed identification of ‘groups of fish industry buyers’ which show variable and special interests in dealing with the topics at hand. In accordance with the Packer, Swartz, Ota, and Bailey (2019) study fisheries seem to approach CSR by following a certain variety of sustainable practices, committing to improve relations with local community organizations. In particular, from a managerial perspective, for the purpose of greater sensitization to the topic, still more collaboration between public institutions, local communities, businesses, and suppliers is needed, so that the questions on the CSR in the fisheries industry spread and become internalized through appropriate information channels (Pollach, Johansen, Ellerup Nielsen, & Thomsen, 2012).…”
Section: Conclusion and Policy Implicationmentioning
confidence: 82%
“…The findings of the research, although in the explorative phase, allowed identification of ‘groups of fish industry buyers’ which show variable and special interests in dealing with the topics at hand. In accordance with the Packer, Swartz, Ota, and Bailey (2019) study fisheries seem to approach CSR by following a certain variety of sustainable practices, committing to improve relations with local community organizations. In particular, from a managerial perspective, for the purpose of greater sensitization to the topic, still more collaboration between public institutions, local communities, businesses, and suppliers is needed, so that the questions on the CSR in the fisheries industry spread and become internalized through appropriate information channels (Pollach, Johansen, Ellerup Nielsen, & Thomsen, 2012).…”
Section: Conclusion and Policy Implicationmentioning
confidence: 82%
“…Second, this research builds a CSR-sustainability framework of the CPEC project, which helps to establish a linkage between CSR and sustainability. While a large body of literature has suggested that CSR has a key role to play in making the community and environment sustainable, there is a lack of full understanding of how CSR should be implemented and how it contributes to the sustainable development [45]. This research remedies the gap by revealing the "black box" of the CSR process and reflecting on the potential of CSR to handle the community issues existing in the transnational project between China and Pakistan.…”
Section: Discussionmentioning
confidence: 96%
“…Uses may include redistributing some wealth "equitability" within their own value systems, but often includes using disproportionate wealth to have disproportionate influence over the decision-making processes. There are many commercial initiatives to adopt more socially responsible business practices (Cashore, 2002;Zucchella and Urban, 2014;Packer et al, 2019). Nevertheless, these, too, focus on using the wealth created through commerce responsibly, whereas intentionally limiting the amount of corporate wealth created is rarely considered "sound business practice."…”
Section: Is There a Way Off The Unsustainability Treadmill?mentioning
confidence: 99%